Case Report: Improved surgical treatment for breast capsular contracture by the punctiform-incision approach through the nipple - Zheng, Yan; Hu, Yan-Yan; Zhao, Wan-Yi; Wang, Xiao-Feng; Fang, Qing-Qing; Lv, Xiong; Xiang, Chun; Yao, Jian-Min; Tan, Wei-Qiang (Frontiers in Surgery, 2022)
Capsular contracture is one of the most common complications of breast implant, which often leads to secondary surgery. Patients with unconspicuous breast contracture do not need treatment, while for those patients with severe symptoms, a capsule revision surgery is of great necessity, including a total periprosthetic capsulectomy and replacement with a new implant. But if the capsular contracture happens in the submuscular space, it will be very difficult to release it completely, and may lead to more complications such as the damage of surrounding tissue. The new method of pouch can create a new subpectoral plane for the insertion of a new implant instead of a total capsulectomy, but this method is unsuited for patients who has little breast tissue or thin skin. To solve this thorny clinical problem, we invented a double-headed separating instrument and came up with a novel-operation method to release capsular contracture, which opened from the nipple by punctiform-incision approach and caused quite small and undetectable trauma. This operation went off without a hitch, and the postoperative breast shape was good with the breast felt and moved naturally. In addition, there were no significant complications throughout the one-year follow-up period. This case was an excellent demonstration of the novel breast capsular contracture release surgery using our optimized double-headed capsule contracture separator.